Peacemaker - Bruchac, Joseph, 1942- (Dial Books for Young Readers, 2021)
"A twelve-year-old Iroquois boy rethinks his calling after witnessing the arrival of a mystical figure with a message of peace in this historical novel based on the creation of the Iroquois Confederacy"--